Optimasi Sistem Irigasi Dalam Meningkatkan Produktivitas Pertanian Desa. Cibunar, Kecamatan.Cibatu - Adi Susetyaningsih; Sulwan Permana; Yoga Adela (Institut Teknologi Garut, 2026)
The issue of water availability for agriculture has become a major challenge due to climate change and the need for improved water management. Irregular rainfall patterns and frequent water shortages pose a threat to crop productivity and farmers' livelihoods. Therefore, this study aims to analyze the uneven distribution of water availability throughout the year, particularly during the dry season. It also assesses water demand and supply using the FJ Mock method and the CROPWAT 8.0 software.The results of the study show that the dependable discharge of the Citameng IV Weir in April reaches 101.260 liters/second, while the water demand for 200 hectares of rice fields in Cibunar Village is 538.65 liters/second. Further analysis focuses on optimizing the irrigation system to enhance agricultural productivity in Cibunar Village, Cibatu District, Garut Regency.The study recommends the design of a trapezoidal irrigation channel lined with stone to efficiently convey water to agricultural land. For an area of 200 hectares, the proposed channel dimensions include a top width of 4.56 meters, a bottom width of 1.23 meters, a water depth of 0.65 meters, and a freeboard height of 0.46 meters.In addition, the study suggests optimizing irrigation system management by involving local communities and developing a more effective water distribution schedule to prevent conflicts among farmers. The construction of weirs or reservoirs is also recommended to regulate water availability more evenly, thereby improving agricultural productivity.